RESULTS OF PROCESSING OF ASTRONEGATIVES WITH COMMERCIAL SCANNER - Protsyuk, Yu. I.; Kovylianska, O. E.; Protsyuk, S. V.; Andruk, V. N. (Одеські астрономічні публікації, 2014)
Astrometric errors depending on the method of scanning with different spatial resolutions were studied with commercial scanner such as Epson Perfection V750 Pro. Accuracy, time of processing, volume of storage were tested using software package described in (Protsyuk, 2014). The best results of scanning were obtained with a resolution of 1200 – 1600 dpi